ASPECTS OF TRADITIONALISM IN MODERNIST POEMS OF SHAFIEI KADKANI - Seyyed Ali Mousavi; Bahman Nozhat; Abdonaser Nazariani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Creativity and innovation of modernist poems does not mean complete ignorance of tradition and traditional principles. A review on works of modernist poets indicates a kind of dynamic and creative traditionalism in their poems, which is seen in form and meaning field as linguistic antiquity, poetic imaginations, interpretive and thematic adaptations used to create new images, meanings and interpretations in the poem. This study aimed at examining traditional aspects in modernist poems of Shafiei Kadkani in order to find poetic evidences existing in modern and untraditional poems; the obtained results showed that his modern poem is associated with Iranian and Islamic history and culture so he has used ancient tradition of Persian language and literature to make his poems modern and enlightening. The obtained results can be seen at the end of this paper.